2022
DOI: 10.3390/agriculture13010044
|View full text |Cite
|
Sign up to set email alerts
|

Development, Validation, and Evaluation of Partial PST Tractor Simulation Model for Different Engine Modes during Field Operations

Abstract: The objectives of this study are the development and verification of a simulation model of the partial PST (power-shift transmission) tractor based on actual field operations. The PST simulation model was verified for the asphalt driving condition, and performance was evaluated for asphalt driving, plow, and rotary tillage. In this study, the traditional, APS (Auto Power Shift) ECO, and APS power engine modes were used to analyze fuel consumption. The statistical analysis proved that the experimental and simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
0
0
Order By: Relevance
“…Tests carried out by Siddique et al (2023) on an agricultural tractor with the power-shift transmission in traditional driving mode, Power and ECO during plow tillage, rotary and asphalt conditions showed excellent fuel economy to ECO mode for all field conditions. The results showed savings between 44.7 and 21.4% (asphalt), 25.9 and 19.6% (plow tillage) 42.4 and 28.4 (rotary tillage) for ECO mode compared to Power and Power mode compared to traditional, respectively.…”
Section: Resultsmentioning
confidence: 96%
“…Tests carried out by Siddique et al (2023) on an agricultural tractor with the power-shift transmission in traditional driving mode, Power and ECO during plow tillage, rotary and asphalt conditions showed excellent fuel economy to ECO mode for all field conditions. The results showed savings between 44.7 and 21.4% (asphalt), 25.9 and 19.6% (plow tillage) 42.4 and 28.4 (rotary tillage) for ECO mode compared to Power and Power mode compared to traditional, respectively.…”
Section: Resultsmentioning
confidence: 96%
“…The fuel consumption in the APS ECO mode was 19.39 L/h. Siddique et al [19] conducted similar research and stated that the APS ECO mode was the most economical engine mode comparison with the conventional and APS power modes; it was around 42.35% more economical in terms of fuel than the conventional mode. However, it was observed that the conventional mode consumed the least fuel during rotary tillage.…”
Section: Discussionmentioning
confidence: 94%
“…Siddique et al [18] estimated fuel consumption based on the engine load levels by using a PTO (power take-off) dynamometer test and developed the simulation model using AMESim software (version 16, SIEMENS AG, Munich, Germany); the correlations were statistically analyzed and compared with those in the previous literature. Siddique et al [19] also stated that tractor fuel consumption highly depends on the load that occurs during agricultural operations and the gear stages used for the operations. In their study, fuel consumption was analyzed in both a simulation model and an experimental field test, and the results were statistically correlated.…”
Section: Introductionmentioning
confidence: 99%